1986
DOI: 10.1007/bf00178510
|View full text |Cite
|
Sign up to set email alerts
|

Fluphenazine plasma levels in patients receiving low and conventional doses of fluphenazine decanoate

Abstract: Plasma fluphenazine concentrations (FLU) were measured in 45 patients with schizophrenic disorders who participated in a double-blind comparison of 5 and 25 mg fluphenazine decanoate (FD). The rise in plasma level of FLU 24 h after a "test dose" was significantly correlated with steady state FLU concentration at 12 weeks (for 5 mg patients, r = 0.45, P = 0.04; for 25 mg, r = 0.78, P = 0.005). Patients who had low FLU at baseline required nearly 6 months to reach a steady state when they received 25 mg. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The rise in mean plasma levels of fluphenazine in patients receiving the 25 mg dose ( Fig. 2A) over a period of 6 months is consistent with our previous report that it took 3-6 months to reach steady state on this dosage regimen (Marder et al 1986). In contrast, there was a decline in mean plasma levels of the sulfoxide over the same time period in the high dose patients (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…The rise in mean plasma levels of fluphenazine in patients receiving the 25 mg dose ( Fig. 2A) over a period of 6 months is consistent with our previous report that it took 3-6 months to reach steady state on this dosage regimen (Marder et al 1986). In contrast, there was a decline in mean plasma levels of the sulfoxide over the same time period in the high dose patients (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Chief among these is that the long half-life of these compounds makes dose titration difficult. Since steady-state levels may not be achieved for 6 months with depot neuroleptics (Marder et al 1986), plasma concentrations may creep up (or down) during this interval following dosage changes, without the clinician’s realizing that the patient’s true exposure to medication effects is changing despite a seemingly steady rate of administration. The use of depot neuroleptics is also complicated by the fact that conversion values between oral neuroleptics and their depot counterparts are less than perfectly worked out (Schooler et al 1980; Yadalam and Simpson 1988).…”
Section: Neuroleptic Drugsmentioning
confidence: 99%
“…Thus, in one study, patients receiving biweekly injections of 5 mg fluphenazine decanoate were found to have reached steady state after the first injection because of fluphenazine resulting from prior therapy with fluphenazine decanoate administered before the period of study. On the other hand, patients receiving biweekly injections of 25 mg fluphenazine decanoate appeared to require 3-6 months (6-12 injections) to reach steady state (Marder et al 1986). Similarly, in a group of patients treated with weekly injections of 50 mg fluphenazine decanoate, 10 weeks (ten injections) were required to reach steady state (Ereshefsky et al 1984) although from theoretical considerations, these authors predicted a time to steady state of 4-6 weeks.…”
Section: Fluphenazine Enanthate and Decanoatementioning
confidence: 90%